The Implementation of Collaborative Writing Technique to Improve Students’ Writing Performance and Soft Skill - Yanti Sri Rezeki; Eka Fajar Rahmani (VELES Voices of English Language Education Society, 2021)
The purpose of this study was to look into the use of collaborative writing techniques to help higher secondary students enhance their writing skills and soft skills. This was done based on the findings of earlier studies that showed the effectiveness of collaborative writing techniques in increasing students' writing abilities and soft skills development. Students in Grade 10 at Sekolah Tunas Bangsa Kubu Raya participated in the study, which used a mixed-methods research methodology. For qualitative data, an observation checklist and field note was used, while for quantitative data, a questionnaire and writing tasks were used. The researchers discovered that collaborative writing was effective in improving students' writing proficiency and soft skills after they evaluated and calculated the data. (1) improvements in writing task mean scores from 78.67 in Meeting 1 to 87.13 in Meeting 3; (2) students' responses on a questionnaire about their writing ability and soft skills reached 92 percent in elaborating ideas and 93 percent in gaining self-esteem and confidence; (3) improvements in observation checklists that were performed excellently (scale 4) by the observers on the third meeting; and (4) the note taker's complimentary comments on the field notes about the pupils' writing abilities and soft skills As a result of this data, it is suggested that collaborative writing techniques be used with higher secondary students to improve both writing performance and soft skills.